Togo : Interim Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2008)
From 2001, Togo has been engaged in the process of preparing its poverty reduction strategy paper (PRSP). As a result of the social and political crisis, Togo's economy has been affected severely. To overcome this crisis, the government has been engaged in key reforms intended to restore harmony to the political climate and focused on restoring financial aid. The measures contained in this interim strategy paper lay the groundwork for improving the public policies/programs required to make progress toward achieving the Millennium Development Goals (MDGs).